The variable European Little Ice Age. (1st July 2022) - Wanner, Heinz; Pfister, Christian; Neukom, Raphael
Abstract: The Little Ice Age (LIA), which lasted from about 1250 to 1860 AD, was likely the coldest period of the last 8000 years. Using new documentary data and analyses of alpine glacier fluctuations, the complex transition from the Medieval Climate Anomaly to the LIA and the ensuing high variability of seasonal temperatures, are described and interpreted for Europe. The beginning of the LIA was likely different in both hemispheres. The low temperature average of the LIA is primarily due to the high number of cold winters. Conversely many summers were warm and dry. Important triggers of the lower temperatures were, primarily, the numerous clusters of volcanic eruptions and the weak solar irradiance during the four prominent Grand Solar Minima: Wolf, Spörer, Maunder, and Dalton. The drop in temperature triggered the sea-ice–albedo feedback and led to a weakening of the Atlantic overturning circulation, possibly associated with a trend towards negative North Atlantic Oscillation indices. The statistics of extreme events show a mixed picture. Correlations with forcing factors are weak, and can only be found in connection with the "Years without a Summer", which very often occurred after large volcanic eruptions. Highlights: The European Little Ice Age was mostly a winter phenomenon. It was mainly triggered by groups of volcanic eruptions and four Grand Solar Minima. Cold and humid summers often occurred after massive volcanic events. Extremely cold winters were often related to a negative North Atlantic Oscillation. Three large Alpine glacier advances occurred around 1380, 1680 and 1860 AD.